UNDERSTANDING HUMAN NATURE: AN INTEGRATIVE APPROACH FROM PHILOSOPHICAL AND RELIGIOUS PERSPECTIVES - Arifin, Nurul (al-Lubb: Journal of Islamic Thought and Muslim Culture, 2025)
This study examines human nature from two complementary perspectives: philosophy and religion. Philosophy views humans as rational, moral, and existential beings capable of critical thinking and self-reflection. Religion, on the other hand, perceives humans as God's creation with spiritual dimensions and divine purposes. While these perspectives differ in their epistemological approaches philosophy relying on reason and religion on revelation they share common ground in recognizing human dignity, moral responsibility, and the search for meaning. This research explores the convergence and divergence between philosophical and religious understandings of humanity, demonstrating how both can be integrated to form a comprehensive view of human existence.